Vulcanization Kinetics of Natural Rubber Based On Free Sulfur Determination - Abu Hasan; Rochmadi Rochmadi; Hary Sulistyo; Suharto Honggokusumo (Indonesian Journal of Chemistry, 2013)
The determination of free sulfur in the rubber vulcanizates provided significant representation of vulcanization reaction. In this research, the effects of vulcanization temperature, the mixing method of carbon black into rubber, the ingredients mixing sequence and the type of carbon black were studied on masticated and milled natural rubber in which the reaction was observed by un-reacted sulfur determination. The results showed that higher vulcanization temperature provided faster vulcanization reaction and greater reaction rate constant. Similarly, the mixing sequence of ingredient and carbon black into rubber influenced the rate of vulcanization reaction. The subsequent ingredients mixing sequence, in this case, resulted in higher vulcanization rate compared to that of the simultaneous one. However, the mixing method of carbon black into rubber brought small effect on the rate of vulcanization reaction. The type of carbon black applied was observed to influence the reaction rate of vulcanization. Smaller particle sizes of carbon black gave larger reaction rate constant. In this case, the type of carbon black N 330 gave faster vulcanization rate than that of N 660.